Lower-limb strength and power characteristics in relation to 180° change of direction ability in elite female basketball players - Ogata, H.; Yamashita, D.; Nishikawa, N.; Yokozawa, T.; Hoshikawa, M. (Frontiers in Sports and Active Living, 2025)
This study examined the relationships among lower-limb strength, power, and horizontal ground reaction force (GRF) during change of direction (COD) tasks in elite female basketball players. Sixteen athletes completed an isometric mid-thigh pull (IMTP), a countermovement jump (CMJ), a lateral shuffle, and 180° turns. For the COD task, the turning distance was individualized based on each participant's standing height. Dual portable uniaxial force-plates were used to measure IMTP peak force and the rate of force development (RFD) over 0-200 ms (RFD200) and 0-250 ms (RFD250). CMJ jump height and phase-specific peak power (braking and propulsive) were also quantified, with all variables normalized to body mass. Horizontal GRFs during plant-foot contact in the COD tasks were recorded using triaxial force-plates, and both peak and mean GRF relative to body mass were analyzed. Mean horizontal GRF during both the lateral shuffle and the 180° turn showed consistent, significant positive correlations with IMTP peak force (r = 0.56-0.80, all p < 0.05). In contrast, correlations between mean horizontal GRF and IMTP RFD were limited, reaching significance only during the right lateral shuffle (RFD250: r = 0.51, p = 0.04) and the left 180° turn (RFD200 and RFD250: both r = 0.68, p < 0.01). Peak horizontal GRF showed negligible associations with most IMTP or CMJ variables, except for IMTP peak force during the left 180° turn (r = 0.51, p = 0.045). Associations with CMJ metrics were modest; jump height correlated significantly with mean horizontal GRF only during the right lateral shuffle (r = 0.50, p = 0.047), whereas CMJ peak braking and propulsive power showed no significant relationships. These findings emphasize the importance of maximal isometric strength for COD performance in this population and highlight the need to select assessment indices aligned with the task-specific demands of strength and conditioning programs.